Analisis Kerjasama Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK) dalam The Egmont Group Terhadap Penanganan Pendanaan Terorisme di Indonesia - Muhammad Jasuma Fadholi; Ika Riswanti Putranti; Sheiffi Puspa Pertiwi (Journal of International Relations Diponegoro, 2017)
Indonesia is a potential country for terrorist acts and its funding, thus made FATF Reccomendations as a guide. It was reflected on the establishment of the Indonesian Financial Transaction Report and Analysis Center (INTRAC) in 2002 and joined The Egmont Group in 2004. The objective of this thesis is to understand the background of cooperation of INTRAC in The Egmont Group against terrorist financing. Through the concept of intersubjectivity in constructivism, this thesis provides descriptive analysis on the background of such cooperation. In addition, this thesis uses the concept of transgovernmental organization to explain the contribution of the cooperation, related to the countering terrorist financing. The result of this thesis shows intersubjectivity in The Egmont Group in form of similarities between FIU’s interest. Collective identity explains terrorist financing as a transnational crime and The Egmont Group as a organization of FIU cooperation in countering terrorist financing, while FATF Recommendations as a international norms. It shapes the interests of Indonesia in countering terrorist financing and implemented through the INTRAC membership in The Egmont Group, while the support of this cooperation is about capacity building through Egmont Plenary Meeting, Egmont Secure Web (ESW) and ISIL Project.